ANALISIS PENGARUH MOTIVASI KERJA TERHADAP PENINGKATAN KUALITAS SUMBER DAYA MANUSIA PADA DAERAH KAMPUNG TAJIR SUMENEP - Ahmad Wahyu; Zainiyatul Afifah; Mudji Kuswinarno (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2024)
The purpose of this study is to investigate how intrinsic motivation at work affects the Tajir of Sumenep's human resource management. The goal of this descriptive quantitative study is to provide a high-level picture of the interrelationships among the variables. Data collection techniques use questionnaires, observation, literature study and documentation study. Questionnaires were distributed to 34 residents of Tajir village, whose responses will be processed and analyzed using instrument tests, descriptive analysis, classical assumption tests and simple regression analysis. The research results reveal that work motivation has a positive impact or has a significant effect on improving the quality of human resources. This is shown if variable X increases or is positive with the assumption of work motivation, the quality of human resources will increase. Human resource quality declines, on the other hand, if variable X falls or is negative relative to the assumption of intrinsic motivation at work. It follows that intrinsic motivation at work significantly boosts Sumenep's tajir village's human resource quality.